![image](https://tex.z-dn.net/?f=1%29+3ax-2x%2B1%2C5a%3D3x%2B7+%5C%5C+3ax%2B1%2C5a%3D5x%2B7+%5C%5C+1%2C5a%282x%2B1%29%3D5x%2B7+%5C%5C+%5Cfrac%7B3%7D%7B2%7Da%3D%5Cfrac%7B5x%2B7%7D%7B2x%2B1%7D+%5C%5C+a%3D%5Cfrac%7B2%285x%2B7%29%7D%7B3%282x%2B1%29%7D+%5C%5C+%281%29+a%3D0%2C+%5C%5C+5x%2B7%3D0+%5C%5C+5x%3D-7+%5C%5C+x%3D-%5Cfrac%7B7%7D%7B5%7D+%5C%5C+%282%29+a%3C0%2C+%5C%5C+%5Cfrac%7B2%2A5%28x%2B%5Cfrac%7B7%7D%7B5%7D%29%7D%7B3%2A2%28x%2B%5Cfrac%7B1%7D%7B2%7D%29%7D%3C0+%5C%5C+x+%5Cin+%28-%5Cfrac%7B7%7D%7B5%7D%3B-%5Cfrac%7B1%7D%7B2%7D%29+%5C%5C+%283%29+a%3E0%2C+%5C%5C+%5Cfrac%7B2%2A5%28x%2B%5Cfrac%7B7%7D%7B5%7D%29%7D%7B3%2A2%28x%2B%5Cfrac%7B1%7D%7B2%7D%29%7D%3E0+%5C%5C+x+%5Cin+%28-%5Cinfty+%3B+-%5Cfrac%7B7%7D%7B5%7D%29+%5Ccup+%28-%5Cfrac%7B1%7D%7B2%7D%3B%2B%5Cinfty+%29+%5C%5C+%5C%5C+%5C%5C+2%29+3%28a-5%29x%3D8-1%2C1a+%5C%5C+3ax-15x%3D8-1%2C1a+%5C%5C+3ax%2B1%2C1a%3D15x%2B8+%5C%5C+a%283x%2B1%2C1%29%3D15x%2B8+%5C%5C+a%3D%5Cfrac%7B15x%2B8%7D%7B3x%2B1%2C1%7D+%5C%5C+%281%29+a%3D0%2C+%5C%5C+15x%2B8%3D0+%5C%5C+15x%3D-8+%5C%5C+x%3D-%5Cfrac%7B8%7D%7B15%7D+%5C%5C+%282%29+a%3C0%2C+%5C%5C+%5Cfrac%7B15%28x%2B%5Cfrac%7B8%7D%7B15%7D%29%7D%7B3%28x%2B%5Cfrac%7B11%7D%7B30%7D%29%7D%3C0+%5C%5C+x+%5Cin+%28-%5Cfrac%7B8%7D%7B15%7D%3B-%5Cfrac%7B11%7D%7B30%7D%29+%5C%5C+%283%29+a%3E0%2C+%5C%5C+%5Cfrac%7B15%28x%2B%5Cfrac%7B8%7D%7B15%7D%29%7D%7B3%28x%2B%5Cfrac%7B11%7D%7B30%7D%29%7D%3E0+%5C%5C+x+%5Cin+%28-%5Cinfty%3B+-%5Cfrac%7B8%7D%7B15%7D%29+%5Ccup+%28-%5Cfrac%7B11%7D%7B30%7D%3B%2B%5Cinfty%29)
0, \\ \frac{2*5(x+\frac{7}{5})}{3*2(x+\frac{1}{2})}>0 \\ x \in (-\infty ; -\frac{7}{5}) \cup (-\frac{1}{2};+\infty ) \\ \\ \\ 2) 3(a-5)x=8-1,1a \\ 3ax-15x=8-1,1a \\ 3ax+1,1a=15x+8 \\ a(3x+1,1)=15x+8 \\ a=\frac{15x+8}{3x+1,1} \\ (1) a=0, \\ 15x+8=0 \\ 15x=-8 \\ x=-\frac{8}{15} \\ (2) a<0, \\ \frac{15(x+\frac{8}{15})}{3(x+\frac{11}{30})}<0 \\ x \in (-\frac{8}{15};-\frac{11}{30}) \\ (3) a>0, \\ \frac{15(x+\frac{8}{15})}{3(x+\frac{11}{30})}>0 \\ x \in (-\infty; -\frac{8}{15}) \cup (-\frac{11}{30};+\infty)" alt="1) 3ax-2x+1,5a=3x+7 \\ 3ax+1,5a=5x+7 \\ 1,5a(2x+1)=5x+7 \\ \frac{3}{2}a=\frac{5x+7}{2x+1} \\ a=\frac{2(5x+7)}{3(2x+1)} \\ (1) a=0, \\ 5x+7=0 \\ 5x=-7 \\ x=-\frac{7}{5} \\ (2) a<0, \\ \frac{2*5(x+\frac{7}{5})}{3*2(x+\frac{1}{2})}<0 \\ x \in (-\frac{7}{5};-\frac{1}{2}) \\ (3) a>0, \\ \frac{2*5(x+\frac{7}{5})}{3*2(x+\frac{1}{2})}>0 \\ x \in (-\infty ; -\frac{7}{5}) \cup (-\frac{1}{2};+\infty ) \\ \\ \\ 2) 3(a-5)x=8-1,1a \\ 3ax-15x=8-1,1a \\ 3ax+1,1a=15x+8 \\ a(3x+1,1)=15x+8 \\ a=\frac{15x+8}{3x+1,1} \\ (1) a=0, \\ 15x+8=0 \\ 15x=-8 \\ x=-\frac{8}{15} \\ (2) a<0, \\ \frac{15(x+\frac{8}{15})}{3(x+\frac{11}{30})}<0 \\ x \in (-\frac{8}{15};-\frac{11}{30}) \\ (3) a>0, \\ \frac{15(x+\frac{8}{15})}{3(x+\frac{11}{30})}>0 \\ x \in (-\infty; -\frac{8}{15}) \cup (-\frac{11}{30};+\infty)" align="absmiddle" class="latex-formula">